2005
DOI: 10.1002/path.1710
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology of HOX genes and their role in cancer

Abstract: The HOM-C clustered prototype homeobox genes of Drosophila, and their counterparts, the HOX genes in humans, are highly conserved at the genomic level. These master regulators of development continue to be expressed throughout adulthood in various tissues and organs. The physiological and patho-physiological functions of this network of genes are being avidly pursued within the scientific community, but defined roles for them remain elusive. The order of expression of HOX genes within a cluster is co-ordinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
220
0
40

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(264 citation statements)
references
References 144 publications
(116 reference statements)
4
220
0
40
Order By: Relevance
“…Consistent with this, gene expression profiling of samples from AML patients with t(8;16)(p11;p13) revealed a characteristic pattern of Hox gene expression, with elevated levels of HOXA9, HOXA10 and MEIS1 (Camos et al, 2006). Increased expression of these proteins has been linked to leukemia induction (Grier et al, 2005). TIF2 (transcription intermediary factor 2) is a third fusion partner identified for MOZ.…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 57%
See 1 more Smart Citation
“…Consistent with this, gene expression profiling of samples from AML patients with t(8;16)(p11;p13) revealed a characteristic pattern of Hox gene expression, with elevated levels of HOXA9, HOXA10 and MEIS1 (Camos et al, 2006). Increased expression of these proteins has been linked to leukemia induction (Grier et al, 2005). TIF2 (transcription intermediary factor 2) is a third fusion partner identified for MOZ.…”
Section: Moz and Morf In Leukemia Leiomyomata And Other Malignanciesmentioning
confidence: 57%
“…Moreover, expression of c-kit, c-Mpl and HoxA9 is reduced. HoxA9 is a key player in hematopoiesis and leukemogenesis (Grier et al, 2005), and its nuclear localization is promoted by thrombopietin, the ligand of c-Mpl (Kirito et al, 2004). Moreover, there is a genetic interaction between c-kit and c-Mpl in repopulating hematopoietic stem cells (Antonchuk et al, 2004).…”
Section: Moz and Morf In Mouse And Zebrafish Developmentmentioning
confidence: 99%
“…Spatiotemporal aberrations in HOX gene expression have been found with polycystic ovarian syndrome (PCOS), endometriosis, hydrosalpinges, and endocrine disrupters that compromise reproduction [8,29]. Moreover, there is accumulating evidence that HOX genes play important roles in oncogenesis, including ovarian cancer progression [30]. However, the specific role of HOX genes in granulosa cell function and oncogenesis has not been extensively explored.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis showed the expression level of HOXA7 was significantly higher in the granulosa tumor cell line, KGN, compared to primary hGCs and SVOG cells. It has been reported that many cancers, including leukemia, colon, skin, prostate, breast and ovarian cancers, have shown alterations in the expression patterns of HOX genes [30,32]. The overexpression of HOX genes has been widely associated with a variety of ovarian carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In human HOX gene family, there are four clusters (A, B, C, and D) located on four different chromosomes (7p15, 17p21, 12q13, and 2q31, respectively) 4, 5. There are 39 HOX genes in HOX gene family, and these genes are assigned to 13 paralog groups in each cluster, based on the position within the cluster and the homeobox sequence similarity.…”
Section: Introductionmentioning
confidence: 99%